PENGARUH RESPONSIVITAS DAN AKUNTABILITAS LAYANAN PANDAWA TERHADAP KEPUASAN PENGGUNA PADA BPJS KESEHATAN KOTA BANDAR LAMPUNG - Mahya Lydia Lestari; Asmaria Asmaria; M. Harviend Gilang Perdana; Erwin Putubasai (CV. Denasya Smart Publisher, 2025)
This study aims to analyze the influence of responsiveness and accountability of the PANDAWA service (Administrative Services via WhatsApp) on the satisfaction of BPJS Health users in Bandar Lampung City. The main focus of this study is to determine the extent to which these two variables, both partially and simultaneously, contribute to the level of satisfaction of digital service users of BPJS Health. According to Zeithaml and colleagues, the dimension of responsiveness has several important indicators. The ability to serve each user who needs services quickly and accurately, ensuring that services are delivered on time, and responding to all user complaints are included in these indicators. The research method used is a quantitative approach with the distribution of questionnaires to 400 respondents selected using Slovin's formula from a total population of 1,071,331 people. The data analysis technique was carried out using SPSS 25 software. The research results indicate that the responsiveness of PANDAWA services has a positive and significant effect on user satisfaction (t calculated = 10.887; sig. = 0.000), as does service accountability (t calculated = 7.635; sig. = 0.000). Simultaneously, responsiveness and accountability together also have a significant effect on user satisfaction (F calculated = 245.916; sig. = 0.000). The implications of these findings suggest that improving the quality of responsiveness and accountability simultaneously is very important to create a satisfying service experience for the public. Therefore, BPJS Kesehatan needs to continue optimizing both aspects in order to enhance effectiveness and satisfaction in PANDAWA's digital services.